Endovascular coiling versus neurosurgical clipping in the management of aneurysmal subarachnoid haemorrhage in the elderly: a multicenter cohort study - Lee, Keng Siang (Springer Science and Business Media LLC, 2024)
10.1007/s10143-024-02325-z